Growth Response Test on Potential Indigenous Bacteria to Degrade Naphthalene and Phenanthrene on various pH - Alfi Rizca Hardianti; Helga Lusiana; Dita Widayanti Sawitri (UNIVERSITAS NEGERI PADANG, 2019)
This study aims to understand the growth response of indigenous bacteria originating from oil sludge in Dumai which has the potential as Naphthalene and Fenantren degrading agents based on variations in substrate pH. The isolates used in this study were Isolate A, Isolate E, and Isolate F as a result of isolation from oil sludge in Dumai. Based on the results of the growth response test on various concentration in previous studies, we chose E isolates to be tested for its degradation ability. The bacterial growth response data was obtained based on OD measurements every 24 hours using a spectrophotometer and TPC at 72 hours using Nutrient Agar media. Based on these data, we determined the optimum pH for indigenous bacterial growth potential to degrade naphthalene or phenanthrene. In all variations of pH, bacterial isolate E experienced growth. This shows that bacterium E can use naphthalene and fenantren at normal pH range (pH 5-9).